Recent Techniques and Applications in Ionizing Radiation Research 2020
DOI: 10.5772/intechopen.92220
|View full text |Cite
|
Sign up to set email alerts
|

Bisphosphonates as Chelating Agents in Uranium Poisoning

Abstract: The study of uranium toxicity is very important for public health in general and especially for workers involved in the processes of uranium mining and milling because of the immediate and/or mediate risks of exposure. Most available studies show unsuccessful attempts to eliminate uranium from target organs once the poisoning has occurred. Our group has managed to avoid damage to target organs (short-term kidney and long-term bone damage) in a high percentage of animals treated with lethal doses of uranyl nitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Although the most obvious effect of U exposure is damage to the proximal convoluted tubules, necrotic cells from the tubular epithelium have also been reported [19]. The histological alterations observed as a result of exposure to UN include partial degeneration, necrosis, and cast formation in proximal convoluted tubule although with damage to brush border, but glomeruli remain intact [47]. In our laboratory, we have observed that kidneys of exposed animals revealed the usual U-induced tubule necrosis lesions with abundant hyaline cylinders and extensive areas of necrosis after 48 h of 350 mg UN/kg b.w.…”
Section: Renal Toxicitymentioning
confidence: 99%
“…Although the most obvious effect of U exposure is damage to the proximal convoluted tubules, necrotic cells from the tubular epithelium have also been reported [19]. The histological alterations observed as a result of exposure to UN include partial degeneration, necrosis, and cast formation in proximal convoluted tubule although with damage to brush border, but glomeruli remain intact [47]. In our laboratory, we have observed that kidneys of exposed animals revealed the usual U-induced tubule necrosis lesions with abundant hyaline cylinders and extensive areas of necrosis after 48 h of 350 mg UN/kg b.w.…”
Section: Renal Toxicitymentioning
confidence: 99%